2010
DOI: 10.1115/1.4001866
|View full text |Cite
|
Sign up to set email alerts
|

Performance Testing of Huber Needles for Coring of Port Septa

Abstract: The Food and Drug Administration received complaints of Huber needles creating cores in the septa of ports of gastric banding devices. One of these complaints represented a cluster of similar events, even though no deviations from design specifications or recommended practices were subsequently identified by the manufacturer. The authors conducted this comparative investigation of off-the-shelf Huber needles and ports from several manufacturers to determine if engineering parameters could be identified that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…One study showed that the recommended angle for needle insertion is 90° to the septum (and therefore to the chamber floor) (15). Contrary to conventional hypodermic needles, the bevel at the tip of the non-coring needle is prevented from coring because it is parallel to the needle shaft.…”
Section: Numerical Modelmentioning
confidence: 99%
“…One study showed that the recommended angle for needle insertion is 90° to the septum (and therefore to the chamber floor) (15). Contrary to conventional hypodermic needles, the bevel at the tip of the non-coring needle is prevented from coring because it is parallel to the needle shaft.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Along with those facts, on September 2010, Vesnovsky et al described how to detect defective needles and how a properly working needle should be shaped. The article also describes a new performance test for Huber needles.…”
Section: Literature Reviewmentioning
confidence: 99%